Young people's experiences of physical activity insecurity: a qualitative study highlighting intersectional disadvantage in the UK - Caroline Dodd-Reynolds; Naomi Griffin; Phillippa Kyle; Steph Scott; Hannah Fairbrother; Eleanor Holding; Mary Crowder; Nicholas Woodrow; Carolyn Summerbell (BMC, 2024)
Abstract Background Intersecting socioeconomic and demographic reasons for physical activity (PA) inequalities are not well understood for young people at risk of experiencing marginalisation and living with disadvantage. This study explored young people's experiences of PA in their local area, and the associated impacts on opportunities for good physical and emotional health and wellbeing. Methods Seven local youth groups were purposefully sampled from disadvantaged areas across urban, rural and coastal areas of England, including two that were specifically for LGBTQ + young people. Each group engaged in three interlinked focus groups which explored young people's perceptions and lived experience of PA inequalities. Data were analysed using an inductive, reflexive thematic approach to allow for flexibility in coding. Results Fifty five young people aged 12-21 years of different sexualities, gender and ethnicity took part. Analysis yielded four themes: PA experiences across spaces; resigned to a lack of inclusivity and 'belonging'; safety first; complexities in access and accessibility. Young people felt more comfortable to be active in spaces that were simpler to navigate, particularly outdoor locations largely based in nature. In contrast, local gyms and sports clubs, and the school environment in general, were spoken about often in negative terms and as spaces where they experienced insecurity, unsafety or discomfort. It was common for these young people to feel excluded from PA, often linked to their gender and sexuality. Lived experiences or fears of being bullied and harassed in many activity spaces was a powerful message, but in contrast, young people perceived their local youth club as a safe space. Intersecting barriers related to deprivation, gender and sexuality, accessibility, disability, Covid-19, affordability, ethnicity, and proximity of social networks. A need emerged for safe spaces in which young people can come together, within the local community and choose to be active. Conclusions The overarching concept of 'physical activity insecurity' emerged as a significant concern for the young people in this study. We posit that PA insecurity in this context can be described as a limited or restricted ability to be active, reinforced by worries and lived experiences of feeling uncomfortable, insecure, or unsafe.